2018
DOI: 10.7326/m18-0852
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Overlapping Opioid and Benzodiazepine Prescriptions Among Veterans Dually Enrolled in Medicare Part D and the Department of Veterans Affairs

Abstract: Background: Overlapping opioid and benzodiazepine use is associated with increased risk of overdose. Veterans receiving medications concurrently from VA and Medicare may be at higher risk of such overlap. Objective: To assess the association between dual use of VA and Medicare drug benefits and receipt of overlapping opioid and benzodiazepine prescriptions. Design: Cross-sectional Setting: VA and Medicare Participants: All Veterans enrolled in VA and Part D filling >2 opioid prescriptions in 2013 (n=36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Dual use is known to increase the likelihood of uncoordinated and poorly managed care, which can increase risk for accidental death from prescription opioid overdose due to duplicative prescriptions. Like prior research (12, 20), our study found higher-intensity opioid use and greater rates of opioid dosages higher than 120 MME among dual users than VA-only or Part D-only users. However, controlling for opioid dose, alcohol and substance use disorders, and RIOSORD measures minimally attenuated the observed effect.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Dual use is known to increase the likelihood of uncoordinated and poorly managed care, which can increase risk for accidental death from prescription opioid overdose due to duplicative prescriptions. Like prior research (12, 20), our study found higher-intensity opioid use and greater rates of opioid dosages higher than 120 MME among dual users than VA-only or Part D-only users. However, controlling for opioid dose, alcohol and substance use disorders, and RIOSORD measures minimally attenuated the observed effect.…”
Section: Discussionsupporting
confidence: 82%
“…Because case and control patients were balanced on all matching variables except age, we also included a categorical age variable as a covariate. We described opioid dose, use of benzodiazepines, and use of other central nervous system depressants but excluded these from the main analysis because prior studies indicate that these variables lie in the causal pathway between exposure and outcome and are thus unsuitable for model adjustment (12, 20, 35).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the US population, 6-13% receive a BZ prescription in any 1 year [8][9][10][11]. In pain management, BZRAs assume a more prominent role being prescribed to 10-33% of persons who are also receiving opioids [12][13][14][15][16][17][18][19]. Of particular concern, use is even greater among those at high risk: the elderly and those who have multiple prescribers, are on at least 200 morphine milligram equivalent (MME) daily opioid doses, or have greater mental health and substance use problems [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%